Contraintes climatiques dans les Préalpes françaises : évolution récente et conséquences potentielles futures - Sylvain Bigot; Sandra Rome (EchoGéo)
The climate of the French Alps remains poorly described, and its interannual variability is difficult to study because of the wide variety of local topoclimatic characteristics and the lack of available long-term time-series. Regional consequences by certain climatic threat on various economic activities are nevertheless expected. This article thus proposes a diagnosis of the contemporary climatic variations (1959-2009) on the scale of French northern Prealps (Vercors and Chartreuse) by using the time series of 4 reference stations. Observed changes are then related to known or potential impacts on the regional socioeconomic activities.